Electroconvulsive therapy during the COVID-19 pandemic - Grover, Sandeep (Indian J Psychiatry, 2020)
The COVID-19 pandemic has forced substantial changes in the practice of psychiatry, including that of electroconvulsive therapy (ECT). There is higher risk of transmission of the SARS-CoV-2 virus during ECT unless due care is taken. However, in many cases, ECT cannot be avoided. In this paper, we discuss various measures that may be adapted to reduce the risk of transmission of the virus during ECT. We also suggest certain modifications to the practice of ECT in order to achieve a balance between risks and benefits of the procedure during the pandemic.